The Asia-Pacific origins of the current outbreaks of Zika virus - Sam, Jamal I-Ching (CSIRO Publishing, 2018)
Zika virus (ZIKV) is a mosquito-borne arbovirus from the Flaviviridae family, first isolated in 1947 from a monkey in Uganda. In the ensuing decades up to the 2000s, there have been sporadic reports of infections and seropositivity in humans in Africa and Asia1,2. The first isolation of ZIKV outside Africa was from Aedes aegypti mosquitoes in Malaysia in 19663. Seropositivity has also been reported in wild monkeys in Malaysia3, although the relevance of this in sylvatic transmission of ZIKV is unknown. These studies suggest that there was endemic and mostly undetected transmission in Asia during this period. Re-emergence from Asia has now brought this relatively neglected virus into the focus of global attention.